La popolarizzazione della politica: ruolo dei media e implicazioni per la cittadinanza (Altre Modernità, 2010)
The merging of political sphere, popular culture and media narrations is one of the most interesting features of today’s political communication on a global scale. The “mediatization” of politics finds its full manifestation in the sweeping process of the popularization of political discourse. The mutual adaptation between television – with its drives for entertainment, spectacle and audience ratings – and politics striving for public attention has generated the “pop politics”. The rise of the so-called infotainment and politainment in the political discoruse addresses the question whether and to what extent this type of political communication affects the civic culture and political participation.